Knowledge Capital and Aggregate Income Differences: Development Accounting for U.S. States - Jens Ruhose; Eric A. Hanushek; Ludger Woessmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Although many U.S. state policies presume that human capital is important for state economic development, there is little research linking better education to state incomes. We develop detailed measures of skills of workers in each state based on school attainment from census micro data and on cognitive skills from state- and country-of-origin achievement tests. These new measures of knowledge capital permit development accounting analyses calibrated with standard production parameters. We find that differences in knowledge capital account for 20-35 percent of the current variation in per-capita GDP among states, with roughly even contributions by school attainment and cognitive skills. Similar results emerge from growth accounting analyses, emphasizing the importance of appropriately measuring worker skills. These estimates support emphasis on school improvement as a strategy for state economic development.
Keywords: O47; I25; J24; 330